Comprehensive study of concrete creep, shrinkage, and water content evolution under sealed and drying conditions. (1st February 2017) - Theiner, Y.; Drexel, M.; Neuner, M.; Hofstetter, G.
Abstract: A comprehensive study of the time‐dependent behaviour of concrete, enhanced by measuring the evolution of the respective mass water content, is presented. Compressive creep as well as shrinkage are investigated on sealed and unsealed specimens in terms of the concrete age at loading of 2, 7, and 28 days, respectively, at a loading level of 30% of the compressive strength at loading. In addition, on the basis of the collected measurement data, the impact of load application on the moisture content is studied and the Pickett effect is re‐examined. The obtained set of material data consists of basic and drying creep strains for different concrete ages at loading, autogenous shrinkage strains as well as combined autogenous and drying shrinkage strains, the evolution of the mass water content, the water desorption isotherm, and the time‐dependent evolution of Young's modulus and the compressive strength. It provides a consistent set of material data for a particular concrete grade and will be available for calibrating and validating concrete models.